Exomic variants of an elderly cohort of Brazilians in the ABraOM database. Issue 7 (3rd May 2017) - Naslavsky, Michel Satya; Yamamoto, Guilherme Lopes; de Almeida, Tatiana Ferreira; Ezquina, Suzana A. M.; Sunaga, Daniele Yumi; Pho, Nam; Bozoklian, Daniel; Sandberg, Tatiana Orli Milkewitz; Brito, Luciano Abreu; Lazar, Monize; Bernardo, Danilo Vicensotto; Amaro, Edson; et al.
Abstract : Genomic variants from highly admixed populations are still underrepresented in public databases. ABraOM is a publicly available web database, currently harboring variants from 609 WES data of an elderly population representative cohort of São Paulo metropolis. Over 200K high confidence variants absent from major databases were identified. About 1% of the individuals carry ACMG possibly actionable LoF variants. Reliable pathogenicity assertions remain challenging and elderly cohorts are an invaluable resource to enhance variant interpretation efficacy. Abstract: Brazilians are highly admixed with ancestry from Europe, Africa, America, and Asia and yet still underrepresented in genomic databanks. We hereby present a collection of exomic variants from 609 elderly Brazilians in a census‐based cohort (SABE609) with comprehensive phenotyping. Variants were deposited in ABraOM (Online Archive of Brazilian Mutations), a Web‐based public database. Population representative phenotype and genotype repositories are essential for variant interpretation through allele frequency filtering; since elderly individuals are less likely to harbor pathogenic mutations for early‐ and adult‐onset diseases, such variant databases are of great interest. Among the over 2.3 million variants from the present cohort, 1, 282, 008 were high‐confidence calls. Importantly, 207, 621 variants were absent from major public databases. We found 9, 791 potential loss‐of‐function variants with about 300 mutations per individual. Pathogenic variants on clinically relevant genes (ACMG) were observed in 1.15% of the individuals and were correlated with clinical phenotype. We conducted incidence estimation for prevalent recessive disorders based upon heterozygous frequency and concluded that it relies on appropriate pathogenicity assertion. These observations illustrate the relevance of collecting demographic data from diverse, poorly characterized populations. Census‐based datasets of aged individuals with comprehensive phenotyping are an invaluable resource toward the improved understanding of variant pathogenicity.